E-cadherin marks a subset of inflammatory dendritic cells that promote T cell-mediated colitis. - Siddiqui, K; Laffont, S; Powrie, F (2010)
Dendritic cells (DCs) play a pivotal role in controlling the balance between tolerance and immunity in the intestine. Gut conditioned CD103(+) DCs promote regulatory T (Treg) cell responses; however, little is known about DCs that drive inflammation in the intestine. Here, we show that monocyte-derived inflammatory DCs that express E-cadherin, the receptor for CD103, promote intestinal inflammation. E-cadherin(+) DCs accumulated in the inflamed mesenteric lymph nodes and colon, had high expression of toll-like receptors, and produced colitogenic cytokines, such as IL-6 and IL-23, after activation. Importantly, adoptive transfer of E-cadherin(+) DCs into T cell-restored immunodeficient hosts increased Th17 cell responses in the intestine and led to exacerbation of colitis. These results identify a monocyte-derived inflammatory DC subset that is associated with the pathogenesis of intestinal inflammation, providing a therapeutic target for the treatment of inflammatory bowel disease.